Improving Community Economic Value Through Utilization of Oil Palm Leaf Midribs into Export Handicraft Products - Yuliza, Mai; Desda, Mia Muchia; Elondri, Elondri; Adriwilza, Adriwilza; Nurhamzah, Nurhamzah; Endarwita, Endarwita; Yurasti, Yurasti; Sari, Ria Widhia; Satriadi, Satriadi; Febianni, Valen; Dini, Dini (Transpublika Publisher, 2024)
This community service activity aims to increase the economic value of the community through the utilization of oil palm leaf midribs that have been underutilized into export-valued handicraft products. Palm oil is a leading commodity in many regions in Indonesia, but the waste in the form of leaf midribs is often neglected. Through training and mentoring programs, the community is able to produce a variety of innovative new designs, following modern market trends. palm oil leaf midribs handicrafts not only have functional value but also a more attractive aesthetic value. In addition, this activity also includes education on international marketing strategies and export market access. The results of the activities showed an increase in community knowledge and skills in processing oil palm leaf midribs and an increase in economic income through marketing products to international markets. This activity is expected to be sustainable and become a model for local resource-based economic development.